The Bacterial Nucleoid: Methods and Protocols - Espéli, Olivier (Methods in molecular biology, 2017)
This volume presents state-of-the-art protocols for key experiments that have revolutionized our understanding of the bacterial nucleoid. This book is divided into five parts: Part I introduces molecular genetic methods to study bacterial nucleoids; Part II highlights the study of bacterial nucleoid with whole genome analysis method; Part III discusses molecular biology methods to study nucleoid structuring factors; Part IV looks at imaging bacterial nucleoid; and Part V explores biophysics of the bacterial nucleoid. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Thorough and cutting-edge, The Bacterial Nucleoid: Methods and Protocols is a valuable resource that provides a wealth of new information about this chromosome.